Inhabiting the extimacy. The home, the burrow, the zone - Calefati, Alessandro; Cimatti, Felice (Itinerari, 2024)
The present paper analyzes three different models of organization of the living space – home, burrow and zone – through the two interconnected operation of inclusion/exclusion on one side, and the relationship between human and non-human on the other side. The main thesis of the paper is that each of these models is co-present with respect to the others, despite the fact that one or the other emerges from time to time, through thresholds of in-differentiation.